The Impact of Iran Phobia on Arms Race in Persian Gulf After 2001 - Pour, Peyman Soleiman (Journal of History Culture and Art Research, 2017)
In the aftermath of the Islamic Revolution in 1979, America's vital interest in the region was seriously challenged. Since this time, the project of Iran-phobia in various fields of military, political, economic, advertising and media, especially in the Western countries and America, was on the agenda and eventually led to the fear of the Islamic Republic of Iran in the Middle East. The main question of this research is that, what is the relation between Iran-phobia and Middle East arms purchases? The hypothesis of this paper is that instilling fear of Iran leads to obtain greater economic benefits for Western countries and America through the sale of weapons to countries in the Middle East. The present article is using new approach as a conceptual framework, and using descriptive and analytical method to evaluate the effect of Iran-phobia on the upward movement of weapons purchases in the Middle East.